2021
DOI: 10.1039/d0tc05004k
|View full text |Cite
|
Sign up to set email alerts
|

Solution-processed organic semiconductor crystals for field-effect transistors: from crystallization mechanism towards morphology control

Abstract: The recent progress in crystallization mechanisms of organic semiconductor crystals and the morphology control strategies associated with the crystallization behaviors are summarized in this review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 120 publications
0
34
0
Order By: Relevance
“…Uncontrolled migration of organic molecules in the solvent and random crystallization behaviour will result in inescapable holes, flaws, and grain boundaries in the crystalline film, and these crystalline features would substantially inhibit crystal liquid phase growth [114]. Exploration of device performance and research into the intrinsic features of OSCs are highly needed.…”
Section: Fabrication Of 2d Organic Crystalsmentioning
confidence: 99%
“…Uncontrolled migration of organic molecules in the solvent and random crystallization behaviour will result in inescapable holes, flaws, and grain boundaries in the crystalline film, and these crystalline features would substantially inhibit crystal liquid phase growth [114]. Exploration of device performance and research into the intrinsic features of OSCs are highly needed.…”
Section: Fabrication Of 2d Organic Crystalsmentioning
confidence: 99%
“…[ 1–28 ] Particularly, several studies have addressed the development of organic small molecules for organic field effect transistors (OFETs), enabling electronic circuit fabrication via inexpensive and potentially high‐throughput solution processes compared with vacuum deposition typical of silicon devices. [ 29–37 ] Organic small molecules are interesting because of well‐defined molecular structure, simple purification, and good batch to batch reproducibility as compared to many organic polymers. [ 38–41 ] To design novel solution processable small molecules several factors need to be considered to enhance charge transport, particularly, they must contain a planar conjugated core to promote π–π stacking through intermolecular orbital overlap, proper orbital energetic for stable charge transport, and have substituents for solution processability.…”
Section: Introductionmentioning
confidence: 99%
“…4 Recently, several studies have been reported on transistors employing supramolecular nanoarchitectures, such as nanowhiskers, nanotubes, nanorods, nanowires, and nanosheets. 1,5,6 A distinct characteristic of almost all these reported transistors is that they transport only a single carrier type, i.e., either holes (p-type) or electrons (n-type). Therefore, simultaneous or selectable transport of electrons and/or holes (ambipolar charge transport) remains a highly desirable device characteristic to be achieved, because this characteristic will be able to facilitate the design of better-performing electronic circuits 7 as well as the demonstration of bifunctional organic devices, such as lightemitting 8 and light-sensing transistors.…”
Section: Introductionmentioning
confidence: 99%